The Christmas coat : memories of my Sioux childhood - Sneve, Virginia Driving Hawk (Holiday House, 2011)
Virginia and her brother are never allowed to pick first from the donation boxes at church because their father is the priest, and she is heartbroken when another girl gets the beautiful coat that she covets. Based on the author's memories of life on the Rosebud Reservation in South Dakota.